Analisis Implementasi Akad Murabahah Penyelesaian Pembiayaan Bermasalah Usaha Mikro Melalui Lelang Agunan di BSI KC Ahmad Yani - Natia Nurfaza; Cupian Cupian; Donny Hardiawan (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study analyzes the implementation of the murabahah contract in resolving Non-Performing Financing (NPF) for micro-enterprises through collateral auction at the Bank Syariah Indonesia (BSI) Ahmad Yani Branch Office, Area Bandung Raya. The primary objective is to analyze the conformity of the auction process with comprehensive Sharia principles (fiqih muamalah), particularly focusing on the final stage of debt resolution. Employing a qualitative-descriptive method, data was gathered through literature review and direct interviews with personnel from the bank's collection and recovery department. The findings indicate that the NPF resolution procedure is conducted systematically and ethically, beginning with warnings, mediation, and intensive restructuring efforts, such as rescheduling and reconditioning, in line with the spirit of ta'awun and Fatwa DSN MUI No. 48/2005. The auction is only performed as a final, likuidatif resort when the customer is non-cooperative or entirely unable to pay after all 3R attempts have failed. Crucially, the process generally aligns with positive regulations and Sharia provisions, including the transparent process of Muzayyadah through KPKNL. Key aspects of Sharia compliance include the bank's commitment to returning any surplus funds from the collateral sale directly to the customer, thereby avoiding ghulul (fraudulent gain), and the provision of the option to waive the remaining debt for customers deemed genuinely unable to fulfill their obligations, in line with Fatwa DSN MUI No 47/DSN-MUI/II/2005. This research provides practical insights for Islamic financial institutions on balancing effectiveness in debt resolution with the imperative of comprehensive Sharia compliance and ethical transactional justice.